2021
DOI: 10.1016/j.xcrm.2021.100406
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting TGF-β and PD-L1 with radiation therapy: The Goldilocks principle

Abstract: In the current issue of Cancer Cell , Lan et al. 1 demonstrate that a bifunctional fusion protein targeting TGF-β and PD-L1 can synergize with radiation therapy to simultaneously augment tumor control and reduce normal tissue toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In comparison with monotherapies, some preclinical studies in mouse models have shown efficacy in the use of molecules that target both PD-L1 and TGF-β. M7824 suppresses tumor growth, metastasis, extends survival, and confers long-term protective antitumor immunity (evaluated in multiple tumor types) [144,145]. M7824 has shown a favorable safety profile and clinical efficacy in phase 1 clinical trials, including patients with advanced solid tumors, NSCLC, recurrent GBM, cervical cancer, metastatic TNBC, heavily pretreated CRC, or human papillomavirus (HPV)-associated cancers [132].…”
Section: Current Approaches To Disrupt Tgf-β Signalingmentioning
confidence: 99%
“…In comparison with monotherapies, some preclinical studies in mouse models have shown efficacy in the use of molecules that target both PD-L1 and TGF-β. M7824 suppresses tumor growth, metastasis, extends survival, and confers long-term protective antitumor immunity (evaluated in multiple tumor types) [144,145]. M7824 has shown a favorable safety profile and clinical efficacy in phase 1 clinical trials, including patients with advanced solid tumors, NSCLC, recurrent GBM, cervical cancer, metastatic TNBC, heavily pretreated CRC, or human papillomavirus (HPV)-associated cancers [132].…”
Section: Current Approaches To Disrupt Tgf-β Signalingmentioning
confidence: 99%